2021
DOI: 10.1021/acssuschemeng.1c02483
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Environmental Assessment of Succinic Acid Production from Sugarcane Bagasse

Abstract: This work presents technoeconomic analysis (TEA) and life cycle assessment (LCA) of a novel biorefinery producing succinic acid (SA) from sugarcane bagasse. The process consists of acid pretreatment, fermentation, followed by downstream separation and purification. Experimental data for pretreatment and fermentation are adapted for a plant processing 4 t/h of dry bagasse, producing 405 kg/h of succinic acid with the same quantity of acetic acid as a side product. Downstream separation is simulated in ASPEN PLU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…In both mid-and high-TRL scenarios, transportation is not typically a significant driver of environmental impacts, but most of the impacts come from other stages, such as agriculture or bioprocessing. This is consistent with previous findings that pointed out these stages to be major drivers of impacts [53,143]. In the case of biomass production, land-use change plays a significant role to the impacts on water consumption and human toxicity, while the biorefinery stage is a major driver of impacts associated with climate change, freshwater eutrophication, and human toxicity.…”
Section: A Case Study To Highlight Trade-offs and Integration Challen...supporting
confidence: 92%
“…In both mid-and high-TRL scenarios, transportation is not typically a significant driver of environmental impacts, but most of the impacts come from other stages, such as agriculture or bioprocessing. This is consistent with previous findings that pointed out these stages to be major drivers of impacts [53,143]. In the case of biomass production, land-use change plays a significant role to the impacts on water consumption and human toxicity, while the biorefinery stage is a major driver of impacts associated with climate change, freshwater eutrophication, and human toxicity.…”
Section: A Case Study To Highlight Trade-offs and Integration Challen...supporting
confidence: 92%
“…For the laboratory fed-batch scenario, the MPSP, GWP100, and FEC of our biorefinery were the lowest reported values thus far for a biorefinery producing SA. Furthermore, for the pilot batch scenario, the biorefinery's MPSP of $1.37/kg [$1.23-1.54/kg; 5th-95th percentiles, hereafter in brackets] was consistently below the reported market price range of $2.53-2.89/kg 30 (adjusted to 2016$) and near the low end of bio-based SA MPSP values ranging from $1.08-3.63/kg reported in the literature 42,43,44,45,46,47,48,49,50 (Fig. 4A).…”
Section: Discussionmentioning
confidence: 75%
“…The GHG emissions of succinic acid produced from various sources of raw materials such as bread waste (Gadkari et al, 2021), corn (Cok et al, 2013), sorghum (Moussa et al, 2016), sugarcane bagasse (Shaji et al, 2021), and fossil fuel (Cok et al, 2013) have been compared with that from EFB as shown in Figure 3. Producing bio-based succinic acid emits GHGs ranging from 0.87 to 1.39 kg CO2 eq/kg bio-based succinic acid.…”
Section: Environmental Impact Assessmentmentioning
confidence: 99%